2019
DOI: 10.1103/physrevd.99.094024
|View full text |Cite
|
Sign up to set email alerts
|

Yang-Mills ghost propagator in linear covariant gauges

Abstract: From first principles, using a screened expansion, a simple one-loop analytical expression is provided for the ghost propagator of pure SU(3) Yang-Mills theory in a generic linear covariant gauge. At variance with the Landau gauge, the ghost dressing function is suppressed in the infrared and vanishes at p = 0, as predicted by other approaches in the continuum. However, in the very limited range where lattice data are available no detectable deviation is found from the Landau gauge, thus reconciling some recen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…In this respect, the appearance of F(0) in our expressions, through the function f 2 (x) of Eq. (3.2), is puzzling, given that for R ξ gauges other than Landau the ghost dressing function has been found to vanish at the origin [75,116,117], which would seem to leave f 2 (x) undefined. It must be noted, however, that the ingredients originating from the ghost-gluon scattering kernel in the STI could behave very differently away from the Landau gauge, possibly introducing divergences that would compensate the vanishing F(0), yielding finally a well-defined ODE.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the appearance of F(0) in our expressions, through the function f 2 (x) of Eq. (3.2), is puzzling, given that for R ξ gauges other than Landau the ghost dressing function has been found to vanish at the origin [75,116,117], which would seem to leave f 2 (x) undefined. It must be noted, however, that the ingredients originating from the ghost-gluon scattering kernel in the STI could behave very differently away from the Landau gauge, possibly introducing divergences that would compensate the vanishing F(0), yielding finally a well-defined ODE.…”
Section: Discussionmentioning
confidence: 99%
“…By direct inspection, and with the help of Tables I, II, and III, one can find that the most general counterterm with vanishing Q charge is of the form Terms containing the parameters of the model are forbidden in Δ due to their BRST doublet structure in Eq. (19). Also, as in usual Yang-Mills theories gauged in a linear covariant wayà la Faddeev-Popov, the linear and quadratic terms in A μ mixed with other fields vanish because of the BRST invariance.…”
Section: Renormalizability Of the Center-vortex Free Sectormentioning
confidence: 91%
“…which is invariant under the extended transformations in Eq. (19). The full action in the flavor sector is the following:…”
Section: The Ym Quantization On the V(s 0 ) Sectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…While in principle the failure of ordinary PT to describe the gluon's infrared mass could be attributed to its break down at low energies, in recent years a new approach to the perturbation theory of pure Yang-Mills (YM) theory has shown that most of the nonperturbative content of the gluon dynamic -at least as far as the two-point functions are concerned -can be absorbed into a shift of the expansion point of the Yang-Mills perturbative series. This approach, termed the screened massive expansion [47][48][49][50][51][52][53][54][55][56][57][58], is a simple extension of ordinary PT, formulated in such a way as to treat the transverse gluons as massive already at tree level while leaving the total action of the theory unchanged. The screened expansion has proven to be self-consistent to one loop -since it is renormalizable and leads to an infraredfinite and moderately small running coupling constant [57] -and predictive when optimized by principles of gauge invariance [54]; it yields two-point functions which are in excellent agreement with the lattice data in the Landau gauge [54,57].…”
Section: Introductionmentioning
confidence: 99%